Study on morphology and growth of water–ice grains spontaneously generated in a laboratory plasma. (May 2015) - Chai, Kil-Byoung; Bellan, Paul M.
Abstract: An apparatus has been developed to study the nucleation, growth, and morphology of water–ice grains spontaneously generated in a weakly ionized plasma having very cold neutral particles. Nucleation of water–ice grains in the laboratory experiment occurs only when plasma exists but the plasma density is not too high. Nonspherical, fast growth occurs when the mean free path of water molecules exceeds the screening length for the ice grain in which case molecules incident on the ice grain can be considered to have collisionless trajectories. High water vapor pressure enhances this nonspherical, fast growth provided the collisionless condition is satisfied. Magnetic field impedes nonspherical growth by reducing the charge residing on water–ice grains if the field is sufficiently strong to make the electron gyro radius smaller than the ice grain screening length. Highlights: Measurements of morphology and growth rate of water–ice grains in a laboratory plasma. Fast, non-spherical growth of water–ice grains occurs in the collisionless regime. High water vapor pressure enhances nonspherical growth provided collisionless condition is satisfied. Magnetic field impedes nonspherical growth if it is strong enough to magnetize electrons.